Feasibility and Acceptability of PcyCare: A Self-Directed Digital Platform for Maternal Health Literacy and Emotional Support - Nurul Jannah; Gunavathy Selvarajh; Sri Lestari (International Journal of Nursing Information, 2025)
The digital transformation in healthcare has driven the emergence of maternal health platforms as strategic innovations that bridge the gap between the limitations of conventional educational methods and the demands of modern emotional support. This study aims to evaluate the feasibility and acceptability of PcyCare (Pregnancy Care), a self-directed digital platform designed to integrate maternal health literacy and emotional support. A quantitative approach with a descriptive feasibility study design was employed, involving 123 participants (comprising 110 pregnant women, 8 maternal health experts, and 5 IT specialists) selected through purposive sampling from Malaysia and Indonesia. Theoretically grounded in the Technology Acceptance Model (TAM), data were collected via structured questionnaires and analyzed using descriptive statistics and Scale-Content Validity Indices (S-CVI). Findings reveal that PcyCare achieved high consensus across all domains; technical feasibility received the highest rating (M=4.82,SD=0.06), followed by user experience (M=4.70,SD=0.48) and content quality (M=4.68,SD=0.11). Expert validation yielded an S-CVI of 0.94 for content relevance and 0.96 for technical stability. Integrating literacy and emotional support features significantly enhances user satisfaction and maternal self-management capacity. In conclusion, PcyCare demonstrates clear advantages over conventional methods in terms of accessibility, information clarity, and real-time psychological reassurance. This study contributes to mHealth literature by pioneering the integration of health literacy and emotional support into a single evidence-based digital intervention, offering theory-driven practical guidance for developers and policymakers to create more inclusive and sustainable maternal healthcare systems.